1999
DOI: 10.1128/jvi.73.12.9832-9842.1999
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of Bluetongue Virus VP2 Protein: Role in Cell Entry

Abstract: Segment 2 of bluetongue virus (BTV) serotype 10, which encodes the outer capsid protein VP2, was tagged with the S-peptide fragment of RNase A and expressed by a recombinant baculovirus. The recombinant protein was subsequently purified to homogeneity by virtue of the S tag, and the oligomeric nature of the purified protein was determined. The data obtained indicated that the majority of the protein forms a dimer and, to a lesser extent, some trimer. The recombinant protein was used to determine various biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 27 publications
(34 reference statements)
1
45
0
3
Order By: Relevance
“…The density map shows the protruding nature of the tip domain and its possession of a cavity lined with ÎČ-sheets. The outermost location of this surface rich in ÎČ-sheets suggests that the tip domain is well positioned for the initial encounter of the virus with the host cell plasma membrane (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density map shows the protruding nature of the tip domain and its possession of a cavity lined with ÎČ-sheets. The outermost location of this surface rich in ÎČ-sheets suggests that the tip domain is well positioned for the initial encounter of the virus with the host cell plasma membrane (13).…”
Section: Resultsmentioning
confidence: 99%
“…Even though there is no sequence homology between the rotavirus VP8 and the BTV VP2, our above structural findings suggest that VP2 binds SA, and this assignment was further investigated using biochemical approaches. BTV particles agglutinate erythrocytes of ruminants (15), and VP2 alone is responsible for this activity (13). To determine whether SA is available on the plasma membrane of permissive cells for BTV infection, we stained HeLa cells with fluorescently labeled wheat germ agglutinin (WGA), a lectin that binds SA and N-acetylglucosamine sugar residues (16) Previous biochemical studies have shown that VP5 causes membrane leakiness and that its expression at the cell surface induces cell-cell fusion to produce syncytia upon exposure to low pH, similar to that found in the endosomal milieu (11).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the RT-PCR assay detected erythrocyte-associated AHSV RNA, which was not necessarily infectious. Bluetongue virus, an orbivirus closely related to AHSV, has been shown to be erythrocyte bound [5], and the lifespan of an erythrocyte in the circulation can be in excess of 145 days [6], which may also explain the extended detection of AHSV nucleic acid in the blood of infected horses by RT-PCR. The period during which horses can be infectious to midges is not known but, given the potential importance to virus transmission in the field, this aspect of the pathogenesis of AHSV infection of horses warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The outer capsid is formed from two viral proteins, VP2 and VP5, while the inner core-particle consists of a 'core-surface' layer composed of VP7, which surrounds a sub-core shell composed of VP3. VP2 interacts with host cellsurface receptors serving as a virus-attachment protein while VP5 is involved in host-cell membrane penetration [41,42,43]. The outer capsid proteins are removed during cell entry, and transcriptionally active core particles are released into the cytosol where virus replication occurs [44,45].…”
Section: Introductionmentioning
confidence: 99%